Exploring factors contributing to patient decision-making in the care journey to elective hernia care in Kenya - Helen W. Li; Jesse Kiprono Too; Sarah Nyanchama Nyariki; Charles Nathan Nessle; Sara Malone; Rachel Matsumoto; Teddy Ashibende Aurah; Jeffrey A. Blatnik; JoAnna Hunter-Squires; Ivan Seno Saruni (PLoS ONE, 2025)
Background Capacity for elective general surgical care is an important reflection of a health system’s ability to meet a population’s surgical needs and is currently known to be inadequate in many low- and middle-income countries. Patient agency is a key, understudied factor which shapes how and when patients ultimately decide to engage with formal care. Understanding factors which influence patient care seeking activity can have important implications for how current and future health systems may be utilized. This study aims to explore how patients approach the navigation and triage of their elective hernia condition within the Kenyan surgical care system. Methods We conducted a qualitative study of 38 convenience-sampled patients diagnosed with an elective hernia condition at a tertiary referral hospital in Kenya between November 2023 and March 2024. We utilized Braun and Clarke’s six-step model of thematic analysis to generate key themes across the phases of care seeking, reaching and receiving as modeled in the Three Delays Framework. Results We identified three main cross-cutting themes including (1) the flow of power from patients to providers, and vice versa, take the form of consent or knowledge, respectively; (2) trust is a limited currency required for patients to engage with formal care; and (3) internal and external contextual factors remain the foundation for patient-provider care activities. We incorporated these themes together in a framework which illustrates the cyclical nature by which each factor feeds back on the others, ultimately affecting patient care. Conclusions Fluctuating flows of patient power and trust interacts with existing infrastructural context to influence the ability of a health system to generate care. Recognizing the interaction of these key factors may have important bearing on the successful implementation of any larger systemic efforts or policies to improve access to elective surgical care.